Differences in morphology and colour pattern of shiny cowbird (Molothrus bonariensis) eggs found in nests of two hosts - De La Colina, M.A. (2011)
Genetic differentiation among shiny cowbird (Molothrus bonariensis) females that use different hosts indicates that in this brood parasite, host use is not random at an individual level. We tested whether there exist differences in morphology and coloration between eggs of shiny cowbirds laid in the nests of two different hosts, the chalk-browed mockingbird (Mimus saturninus) and the house wren (Troglodytes aedon). We took morphometric measures of shiny cowbird eggs found in nests of mockingbirds and wrens and analysed their coloration using digital photography and reflectance spectrometry. We found that shiny cowbird eggs found in mockingbird nests were wider and more asymmetric than those found in wren nests. In addition, cowbird eggs coming from mockingbird nests were brighter and had higher relative red reflectance than those coming from wren nests. Our results show that shiny cowbird eggs laid in nests of two different hosts vary in shape and background colour, but not in spotting pattern. © 2011 The Linnean Society of London.